Study of soil bacteria and fungi population in oil palm with big hole planting system - Rizki Desika Putri Pane; Rana Farrasati; Nuzul Hijri Darlan; Suroso Rahutomo; Heri Santoso; Eko Noviandi Ginting; Iput Pradiko; Fandi Hidayat (The East Java Biological Society, 2022)
The big hole planting system for oil palm is one of the efforts to control the infection of Ganoderma boninense. The big hole method can also improve physical and chemical soil properties that affect the soil microbes population and in turn suppress the soil pathogens. However, the information about soil microbes population under the big hole planting method is still limited. This study aimed to compare the population of soil bacteria and fungi in soil samples from oil palm plantations that applied the big hole for 15 years and non big hole (standard) planting method. The population of bacteria and fungi was analyzed using the dilution plate method, while the calculation was based on the total plate count. Based on the results of statistical analysis (P-Value = 0.05), it is known that the mean population of bacteria is significantly different but the mean population of fungi is not significantly different between the big hole and non-big hole planting systems. The population of soil bacteria under the big hole and standard method was 1.6 x 106 cfu/g and 1.1 x 106 cfu/g, respectively. Meanwhile, the population of soil fungi under the big hole method was 9.7 x 104 cfu/g and 7.2 x 104 cfu/g under the standard planting method. Microorganisms in soil are considered important for maintaining soil health and quality, because various microorganisms are involved in important soil functions. In addition, high soil microbial populations will contribute to reducing soil base disease or suppression of soil pathogens.